Prevención de Caídas: ¿Quién está a riesgo? - Sergio Romero (EDIS)
Revised! FCS2227-Span, a 1-page quiz by Sergio Romero, is a Spanish language version of "Fall Prevention: Who's at Risk?" Readers can take this yes-or-no quiz to determine if they are at high risk of falling. Published as part of the Elder Nutrition and Food Safety (ENAFS) program by the UF Department of Family Youth and Community Sciences, May 2006.